Relationship Between Work–Family Conflict and Support on Construction Professionals’ Family Satisfaction: An Integrated Model in Chile - Briguitte Neculman; Leonardo Sierra-Varela; Berta Schnettler; Noé Villegas-Flores (Buildings)
In the construction industry in Chile, workers face high levels of work–family conflict due to demanding working conditions. This study examines the interactions between work–family conflict, perceived family and organizational support, and the legal regulatory framework on the family satisfaction of professionals in this sector. A sample of 500 workers is evaluated using the partial least squares structural equation method (PLS-SEM). The results highlight that both the legal regulatory framework and perceived family support significantly positively affect family satisfaction. Moreover, organizational support is limited in this situation, whereas work–family and family–work conflicts adversely affect family satisfaction. This study provides evidence for the design of labor policies in construction in Chile, emphasizing the importance of strengthening family support and the regulatory framework to improve work–family balance and workers’ well-being.